Nursing staff teamwork and job satisfaction - KALISCH, BEATRICE J.; LEE, HYUNHWA; ROCHMAN, MONICA (Journal of nursing management, 2010)
kalisch bj, lee h & rochman m. (2010) Journal of Nursing Management 18, 938–947 Nursing staff teamwork and job satisfaction Aim  The aim of the present study was to explore the influence of unit characteristics, staff characteristics and teamwork on job satisfaction with current position and occupation. Background  Teamwork has been associated with a higher level of job satisfaction but few studies have focused on the acute care inpatient hospital nursing team. Methods  This was a cross‐sectional study with a sample of 3675 nursing staff from five hospitals and 80 patient care units. Participants completed the Nursing Teamwork Survey (NTS). Results  Participants’ levels of job satisfaction with current position and satisfaction with occupation were both higher when they rated their teamwork higher (P < 0.001) and perceived their staffing as adequate more often (P < 0.001). Type of unit influenced both satisfaction variables (P < 0.05). Additionally, education, gender and job title influenced satisfaction with occupation (P < 0.05) but not with current position. Conclusions  Results of this present study demonstrate that within nursing teams on acute care patient units, a higher level of teamwork and perceptions of adequate staffing leads to greater job satisfaction with current position and occupation. Implications for Nursing Management  Findings suggest that efforts to improve teamwork and ensure adequate staffing in acute care settings would have a major impact on staff satisfaction.